Inovasi Pembelajaran Interaktif Pendidikan Agama Kristen dalam Menjawab Gaya Belajar Generasi Alpha - Sarah Gracia Lumbantobing; Rudy Roberto Walean (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2026)
The development of the digital era has shaped the characteristics of Generation Alpha, who have an interactive, visual, and technology-based learning style, thus demanding a transformation in the learning process, including in Christian Religious Education. However, the practice of Christian Religious Education learning still tends to be conventional, teacher-centered, and does not accommodate the learning needs of today's students. The mismatch between the learning approach and the characteristics of Generation Alpha has the potential to hinder the involvement and in-depth understanding of students' faith. This study aims to analyze and formulate interactive learning innovations in Christian Religious Education that can address the learning style of Generation Alpha. The research method used is a qualitative method with a literature review approach. The results show that Generation Alpha has the characteristics of an interactive, visual, and technology-based learning style, which has not been fully accommodated in the practice of Christian Religious Education, which still tends to be conventional and teacher-centered. Therefore, concepts and principles of interactive learning are needed that integrate theological and pedagogical approaches in a contextual, participatory, and experiential learning manner. The novelty of this research lies in the formulation of the FAITH Model (Foundation–Active–Interactive–Transformative–Holistic Learning) as a result of conceptual synthesis that integrates theological foundations, active learning, interactive digital technology, transformative reflection, and the application of Christian values into a systematic Christian Religious Education learning framework in accordance with the characteristics of the Generation Alpha learning style. Thus, the FAITH Model offers a conceptual framework for interactive Christian Religious Education learning that is appropriate to the Generation Alpha learning style to support increased learning engagement, understanding of faith, and internalization of Christian values.AbstrakPerkembangan era digital telah membentuk karakteristik Generasi Alpha yang memiliki gaya belajar interaktif, visual, dan berbasis teknologi, sehingga menuntut adanya transformasi dalam proses pembelajaran, termasuk dalam Pendidikan Agama Kristen. Namun, praktik pembelajaran Pendidikan Agama Kristen masih cenderung bersifat konvensional, berpusat pada guru, dan kurang mengakomodasi kebutuhan belajar peserta didik masa kini. Ketidaksesuaian antara pendekatan pembelajaran dengan karakteristik Generasi Alpha berpotensi menghambat keterlibatan serta pemahaman iman peserta didik secara mendalam. Penelitian ini bertujuan untuk menganalisis dan merumuskan inovasi pembelajaran interaktif dalam Pendidikan Agama Kristen yang mampu menjawab gaya belajar Generasi Alpha. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan kajian literatur. Hasil penelitian menunjukkan bahwa Generasi Alpha memiliki karakteristik gaya belajar yang interaktif, visual, dan berbasis teknologi, yang belum sepenuhnya diakomodasi dalam praktik Pendidikan Agama Kristen yang masih cenderung konvensional dan berpusat pada guru. Oleh karena itu, diperlukan konsep dan prinsip pembelajaran interaktif yang mengintegrasikan pendekatan teologis dan pedagogis secara kontekstual, partisipatif, dan berbasis pengalaman belajar. Kebaruan penelitian ini terletak pada perumusan Model FAITH (Foundation–Active–Interactive–Transformative–Holistic Learning) sebagai hasil sintesis konseptual yang mengintegrasikan fondasi teologis, pembelajaran aktif, teknologi digital interaktif, refleksi transformatif, dan penerapan nilai-nilai Kristiani ke dalam satu kerangka pembelajaran Pendidikan Agama Kristen yang sistematis sesuai dengan karakteristik gaya belajar Generasi Alpha. Dengan demikian, Model FAITH menawarkan kerangka konseptual pembelajaran interaktif Pendidikan Agama Kristen yang sesuai dengan gaya belajar Generasi Alpha untuk mendukung peningkatan keterlibatan belajar, pemahaman iman, serta internalisasi nilai-nilai Kristiani.